Regulated expression of galectin-3, a multifunctional glycan-binding protein, in haematopoietic and non-haematopoietic tissues - Sundblad, Victoria (2011)
Galectin-3 belongs to a family of highly conserved animal lectins characterized by their ability to recognize multiple N-acetyllactosamine sequences, which can be displayed on both N- and O-glycans on cell surface glycoconjugates. Although first identified in macrophages, galectin-3 (also called "Mac-2, εBP, CBP35 or L-29") has been found to be widely distributed in several tissues and developmental stages where, depending on its extracellular or intracellular localization, it can display a broad diversity of biological functions including immunomodulation, host-pathogen interactions, embryogenesis, angiogenesis, cell migration, wound healing and apoptosis. In spite of the existence of several reviews describing the multifunctional properties of galectin-3, an integrated view of the regulated expression of this glycan-binding protein in different normal tissues is lacking. Here we attempt to summarize and integrate available information on galectin-3 distribution in normal haematopoietic and non-haematopoietic tissues, mainly in adulthood, with only a brief reference to its expression during embryonic stages. In addition, given the multiplicity of biological roles attributed to this protein, a brief description of galectin-3 functions is also included. Understanding how galectin-3 is regulated in normal tissues will contribute to a rational design of approaches aimed at modulating galectin-3 expression and subcellular localization for experimental and therapeutic purposes.